Acute and physical effects of water-based drilling mud in the marine copepod Calanus finmarchicus. Issue 16 (17th September 2017) - Farkas, Julia; Yvonne Bådsvik, Camilla; Altin, Dag; Nordtug, Trond; Olsen, Anders Johny; Hansen, Bjørn Henrik
ABSTRACT: The aim of this study was to investigate impacts of fine particulate fraction of a commonly used barite-containing drilling mud on the pelagic filter feeding copepod Calanus finmarchicus . The results show that the tested drilling mud had a low acute toxicity on C. finmarchicus (LC50 > 320 mg/L) and that the observed toxicity was likely caused by dissolved constituents in the mud and not the particle phase containing the weighting agent barite. Further, animals were exposed to drilling mud at a concentration of 10 mg/L for 168 hr followed by a 100 hr recovery phase. A rapid uptake of drilling mud particles was observed, while the excretion was slow and incomplete even after 100 hr recovery in clean seawater. The uptake of drilling mud particles caused a significant increase in sinking velocity of copepods, indicating that uptake of drilling mud particles affected their buoyancy. Long-term exposure to low concentrations of drilling mud could therefore cause physical effects such as impacts on the animal's buoyancy which may affect the energy budget of the copepods.